Albanian hidden heritage in Slovenia - Bartulović, Alenka (Traditiones (Ljubljana), 2025)
Focusing on Albanian communities’ overlooked musical heritage in post-Yugoslav Slovenia, this paper analyses how and why the domi-nant framing of Albanians has reinforced the assumption of the absence of the Albanian heritage. By comparing central and peripheral settings in examining the ambivalence towards this heritage in Kočevje and the recent process of heritagisation in Ljubljana, we challenge the notion that minority cultural recognition occurs uniformly across national space.
Keywords: Albanci v Sloveniji; Albanian music; Albanians in Slovenia; albanska glasba; hidden heritage; marginalisation; marginalizacija; performativnost dediščine; pogajanja o dediščini; skrita dediščina; Slovenia; Yugoslavia